Examining experiences concerning goals pursued and smart dimensions to develop in cities on their path to become smart. The case of Costa Rican cities - Pereira Piedra, Isabel Cristina (2023)
The rapid growth of the population in cities has given rise to major urban challenges. This has led city governments to use technical solutions based on Information and Communication Technologies (ICTs), arising the concept of smart city (SC). However, the strategy followed to become smart is still very diffuse. This paper seeks to analyze the opinion of the ICT managers of local governments in their initial stage of cities to become smart. To achieve this aim, we have conducted empirical research in Costa Rican cities, which are initiating the SC process, but emphasizing the technological implementation strategy they are using. Concretely, this paper analyzes variables such as the number of ICT projects, dimensions, goals and expected impacts as well as their association. Findings provide technological strategies that can be used and thus facilitate the implementation process of cities to become smart as well as the achievement of results.